About the elemental analysis of dental implants. (January 2019) - Gonçalves, O.D.; Egito, M.; Castro, C.; Groisman, S.; Basílio, M.; da Penha, N.L.
Abstract: In this paper we present the first results of a broad research line aiming a better understanding about dental implants as the number of procedures, successes and failures in Brazil and possible reasons of losses (from problems on diagnose to fabrication defects from different brands offered in the Brazilian market). One thing that is already evident is the lack of details of the performed elemental analysis of implants, not only in Brazil but also on the majority of reported analyses published on international journals dedicated to the field. There are already a significant number of reports about the composition of dental implants and its surfaces, but in general they have not performed tests enough to validate the results nor reported the procedure with sufficient details establishing their comprehensiveness, which is critical to enable a comparison between those results. One detected problem is the using of a non standard geometry in some equipment that require special shapes or dimension for the analysis. The other is the determination of the uncertainties to be associated to the results. Here we will perform a brief review of the dental implant history, of some problems found in the elemental analysis and will present two sets of measurements, one to investigate the consequences of using nonstandard geometries and another comparing elemental analyses made with different instruments. Highlights: We investigate the influence of sample geometry on the elemental analysis of dental implant. The history and a short review of the area is performed. Elemental analysis of five brass samples with SEM-EDS and WDS. The results show that the geometry has influence on the detected amount of the components. It was found that the uncertainty was larger than the one provided by the equipment.